ANALISIS KOREOGRAFI BEDAYA RETNA DUMILAH KARYA S. NGALIMAN TJONDROPANGRAWIT - Supriyanti, Supriyanti; Meilawanti, Widya Kinanthi Rahayu (Greget: Jurnal Kreativitas dan Studi Tari, 2022)
Bedaya Retna Dumilah is a type of Surakarta-style classical dance danced by seven female dancers. The composer of this dance was S. Ngaliman Tjondropangrawit in 1978. This Bedaya dance is rarely performed. The form of presentation of the Bedaya Retna Dumilah dance is unique and exciting. The uniqueness of this dance lies in the dance moves, floor patterns, accompaniment, and themes. This study aims to analyze and describe the Choreography of the Bedaya Retna Dumilah Dance by S. Ngaliman Tjondropangrawit. The method was carried out by analyzing the visual data of the Bedaya Retna Dumilah Dance video from the text side and conducting interviews using triangulation to obtain valid data. The choreographic approach was analyzed descriptively from form, technique, and content.  S. Ngaliman composed the Bedaya dance with various innovations from movements, floor patterns, timing, themes, poetry, and dance accompaniment. The renewal of this work is necessary so that it can be taught to students in the Dance Study Program, especially for teaching Surakarta Dance classes. The results found from the Choreography of the Bedaya Retna Dumilah Dance are that the theme of the dance is an essential part of composing the Bedaya dance. The piece of romance influences all aspects of the Bedaya Retna Dumilah dance composition. The dance theme also determines the color of the new arrangement of the Bedaya Retna Dumilah dance. S. Ngaliman Tjondropangrawit as a dance master from Surakarta. Significantly skillfully incorporating elements of novelty into the Bedaya Retna Dumilah dance.